2017
DOI: 10.7554/elife.26624
|View full text |Cite
|
Sign up to set email alerts
|

ER retention is imposed by COPII protein sorting and attenuated by 4-phenylbutyrate

Abstract: Native cargo proteins exit the endoplasmic reticulum (ER) in COPII-coated vesicles, whereas resident and misfolded proteins are substantially excluded from vesicles by a retention mechanism that remains unresolved. We probed the ER retention process using the proteostasis regulator 4-phenylbutyrate (4-PBA), which we show targets COPII protein to reduce the stringency of retention. 4-PBA competes with p24 proteins to bind COPII. When p24 protein uptake is blocked, COPII vesicles package resident proteins and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 52 publications
10
102
0
Order By: Relevance
“…Previous studies demonstrated that COPII can form a boundary for the ER quality control machinery (Mezzacasa and Helenius, 2002). A recent finding, consistent with these data, established that COPII is fundamental for ER retention of transport-incompetent proteins (Ma et al, 2017). The data presented in this paper provides a novel mode of action for the COPII complex.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies demonstrated that COPII can form a boundary for the ER quality control machinery (Mezzacasa and Helenius, 2002). A recent finding, consistent with these data, established that COPII is fundamental for ER retention of transport-incompetent proteins (Ma et al, 2017). The data presented in this paper provides a novel mode of action for the COPII complex.…”
Section: Discussionsupporting
confidence: 85%
“…A third construct, GFP-F M 4-GH (Gordon et al, 2010), was fully luminal, contained human growth hormone, and lacked any ER export sequence. Peflin depletions caused a significant decrease in ER export of this bulk flow construct, consistent with a recent study demonstrating that COPII sorting works in part by exclusion of proteins that are not actively included (Ma et al, 2017). This result implies that peflin depletion does not act simply to accelerate vesicle production, but rather stimulates COPII function broadly--including its sorting function.…”
Section: Alg-2/peflin Complexes Affect Er Export Similarly For Multipsupporting
confidence: 90%
“…As abundant constituents of COPII vesicles, the p24 proteins (and associated cargoes) may act simply as molecular ballast to occupy space and thus exclude ER residents and minimize bulk flow. Furthermore, the capacity of these proteins to oligomerize, in coordination with the coat, could additionally facilitate the exclusion of non-cargo proteins through formation of a diffusion barrier (Ma et al, 2017). We find that reducing vesicle size in the p24-depleted background restores the available volume to wild-type levels, and leads to decreased bulk flow even in the absence of p24 function ( Figure 6).…”
Section: Vesicle Morphology and Cargo Occupancy As Drivers Of Qualitymentioning
confidence: 85%
“…In addition to their function as GPI-AP receptors, p24 proteins have also been postulated to function as a quality control filter by modulating the timing of vesicle release (Kaiser, 2000), or by displacing non-specific cargo (Kaiser, 2000;Ma et al, 2017). Here we aimed to better understand the consequences of p24 deletion, focusing on two aspects: membrane bending by Sec31 alone, and selectivity of ER export.…”
Section: Introductionmentioning
confidence: 99%